A safety analysis of elevated highways in Shanghai linked to dynamic load using long-term time-series of InSAR stacks. Issue 12 (2nd December 2019) - Wang, Ru; Yang, Tianliang; Yang, Mengshi; Liao, Mingsheng; Lin, Jinxin
ABSTRACT: Dynamic loads of vehicles have a considerable impact on the safety of elevated highways, but few studies have addressed the influence of dynamic loads on the safety of such linear infrastructure using Time-series SAR Interferometry (TS-InSAR). To fill this gap, we explored the displacement of elevated highways and the possible factors causing the deformation, using a long-term time-series of high resolution TerraSAR-X satellite dataset and Attribution Analysis Model (AAM) associated with dynamic loads for Shanghai, China. The results show that most deformed sections of elevated highways are located on the periphery of the network with a deformation velocity of about −5 mm year −1, as validated by ground-levelling data. Results by the proposed AAM illustrate the displacements of elevated highways correspond to the regional subsiding, dynamic loading, and construction time, as only 5% points are not identified to these factors. This study highlights TS-InSAR can be successfully applied to the safety analysis of operational linear infrastructures.